Peningkatan Keteramipal Menulis Argumentasi Siswa Dengan Menggunakan Media Grafis Flanelgraf Pada Siswa Kelas XI IPA SMAN 4 Pandeglang - Dahlia Dahlia (MENDIDIK: Jurnal Kajian Pendidikan dan Pengajaran, 2017)
This study reviews the importance of media in teaching and learning process, so that the material delivered (message) can be easily understood by the students. But the learning media used must have an element of entertainment. Research method used in this study is experimental method with treatment by level 2 x 2 design. Based on the results of research, there is interaction between vocabulary mastery and flanegraph graphics media use towards student’s argumentation writing skill. And it also affects positively towards argumentation writing skill.